2005
DOI: 10.1159/000084866
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Posterior Fossa Extradural Hematoma – A Rare Complication following Cardiac Surgery

Abstract: Posterior fossa extradural hematoma (PFEDH) is an infrequent condition. Though numerous neuropathological sequelae of cardiopulmonary bypass have been described, to the best of the authors’ knowledge, PFEDH after cardiac surgery has not been reported in the English literature. We report a 4-year-old boy with tricuspid atresia, who underwent cardiac surgery under cardiopulmonary bypass. On the 2nd postoperative day, his neurological condition deteriorated, and a CT scan of the head revealed a large PFEDH with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…[8] Spontaneous EDH following full heparinization during CPB has been reported in the medical literature: In one of those reports, cyanotic congenital heart disease causing coagulation abnormalities was considered as the cause of EDH. [1] Anegawa, et al, reported bifrontal EDH with mass effect in a 12-year-old female following surgery for subaortic stenosis. [3] The causes of space occupying hematoma following CPB could be either full heparinization during surgery and/or associated hypotension during the period of CPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Spontaneous EDH following full heparinization during CPB has been reported in the medical literature: In one of those reports, cyanotic congenital heart disease causing coagulation abnormalities was considered as the cause of EDH. [1] Anegawa, et al, reported bifrontal EDH with mass effect in a 12-year-old female following surgery for subaortic stenosis. [3] The causes of space occupying hematoma following CPB could be either full heparinization during surgery and/or associated hypotension during the period of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports describe EDH following cardiac surgery on CPB. [1][2][3] We describe our experience of EDH following double valve replacement in an adolescent boy.…”
Section: Introductionmentioning
confidence: 99%
“…Brain CT was done, that showed posterior fossa EDH (PFEDH), which is very unusual and rare finding on imaging to occur spontaneously without any history of trauma. According to our best of knowledge previously only 18 cases of spontaneous PFEDH were reported till date since 1951 1 . In past, such case has been reported after cardiac surgery for tricuspid area in 4 years male child 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 8 ] Children have the dura and venous sinuses as opposed to the bones, and bleeding from the venous sinus leads to progressive stripping of the dura from the bone and an expanding PFEDH. Rarely PFEDH is seen in association with other bleeding diathesis,[ 9 10 11 12 ] systemic illness,[ 13 ] after cardiac surgery,[ 14 ] and malignancies such as angiosarcoma,[ 15 ] presenting either spontaneously or after a fall.…”
Section: E Tiopathogenesismentioning
confidence: 99%